NMN reverses D-galactose-induced neurodegeneration and enhances the intestinal barrier of mice by activating the Sirt1 pathway - Lin, Yuxian; Wang, Yajing; Yang, Xinxin; Ding, Ziwei; Hu, Mingye; Huang, Xianfeng; Zhang, Qichun; Yu, Yingcong (Frontiers in Pharmacology, 2025)
BackgroundAge-related decline in nicotinamide adenine dinucleotide (NAD+)—a central regulator of cellular metabolism, DNA repair, and immune homeostasis—is strongly associated with physiological dysfunction. Nicotinamide mononucleotide (NMN), a potent NAD+ precursor, shows promise in counteracting aging-related pathologies, particularly neurodegenerative decline.MethodsAn aging model was established in mice through 8-week D-galactose (D-gal) exposure, followed by NMN oral supplementation. Behavioral outcomes (open field test, Morris water maze) were analyzed alongside oxidative stress markers (SOD, CAT, AGEs), inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-10), and neurotransmitters (LC-MS/MS). Apoptotic activity (TUNEL, p16/p21), mitochondrial regulators (Sirt1, p-AMPK, PGC-1α), and intestinal barrier integrity (HE/AB-PAS staining) were evaluated. Sirt1 dependency was confirmed using inhibitor Ex527.ResultsNMN restored locomotor activity and spatial memory in D-gal mice without altering body weight. Mechanistically, NMN synergistically attenuated oxidative stress and systemic inflammation, elevating antioxidant enzymes (SOD, CAT) and IL-10 while suppressing pro-inflammatory cytokines (TNF-α, IL-6) and AGEs. Cortical/hippocampal analyses revealed reduced apoptosis (TUNEL+ cells) and senescence markers (p16, p21), with enhanced mitochondrial function via Sirt1/AMPK/PGC-1α activation (Sirt1, p-AMPK). NMN concurrently preserved intestinal mucosal architecture, mitigating D-gal-induced barrier disruption. Crucially, all benefits were abolished by Sirt1 inhibition, confirming pathway specificity.ConclusionOur findings establish NMN as a multifaceted therapeutic agent that preserves neurocognitive function and intestinal homeostasis in aging models by orchestrating antioxidative, anti-inflammatory, and antiapoptotic responses through Sirt1/AMPK/PGC-1α activation. This work provides translational insights into NAD+-boosting strategies for age-related disorders.